Microplasma breakdown in GaAs-based avalanche S-diodes doped with deep Fe acceptors - Prudaev, Ilya A. (Physica status solidi B)
The article reports investigations into the microplasma breakdown in GaAs-based avalanche S-diodes doped with deep Fe acceptor impurities. The experiment shows the effect of current limitation in a reverse I–V curve with “soft” avalanche breakdown. It proposes 2D single microplasma models and calculates I–V curves of diodes with a deep impurity during microplasma breakdown. By comparing experimental and calculation data, authors propose an explanation for the effect of current limitation during avalanche breakdown. The effect is associated with capture of avalanche holes at negatively charged Fe centers, which enhances the depletion region and minimizes the maximum electric field in a reverse-biased p–n junction of an S-diode.